FRI0508 Analysis of risk factors of adverse obstetrical outcome in patients with takayasu arteritis. (12th June 2018) - Abisror, N.; Mekinian, A.; Le Guern, V.; Costedoat, N.; ,; Lambert, Marc; Morel, Nathalie; Chapelon, Catherine; Martis, Nihal; Fuzibet, Jean Gabriel; Belenotti, Pauline; Swiader, Laure; et al.
Abstract : Background: Takayasu arteritis (TA) is a large-vessel vasculitis that affects young women of childbearing age. Several small case-series described the pregnancy outcome in TA patients with lack of study determining risk factors associated with adverse pregnancy outcome. Objectives: We performed a French retrospective study, to determine the risk factors associated with obstetrical adverse outcome; and the relation between pregnancy outcome and TA disease activity. Methods: French nationwide retrospective study of pregnancies that lasted at least 12 weeks of gestation (WG) in TA patients. Results: Forty-three pregnancies occurred in 33 patients. The diagnosis of TA was preexisting in 29 patients, and done during pregnancy in 4. For the 39 pregnancies in the 29 patients with a preexisting diagnosis of TA: steroids were maintained throughout pregnancy in 23/39 (59%) with a median dose of 5 mg/day 2–40 immunosuppressive treatment during pregnancy included azathioprine (n=9, 21%) or infliximab (TNF-α antagonist) (n=1, 2%). For the 4 pregnancies with TA diagnosis during, only one was treated by steroids. Aspirin (100 mg/day) was used in 27/43 pregnancies (63%) and antihypertensive drugs were used in 10 pregnancies (23%). Before pregnancy, immunosuppressive treatment had been used in 16 patients: azathioprine (n=10, 30%), methotrexate (n=7, 21%), TNF-α antagonist (infliximab in 3 and adalimumab in 1; n=4, 12%) and cyclophosphamide (n=2, 6%). Maternal adverse events were noted in 20 pregnancies (47%). The most frequent adverse event was arterial hypertension (n=12; 28%): 10 worsening of previous arterial hypertension and 2 de novo arterial hypertension. Other adverse events included pre-eclampsia (n=3; 7%), HELLP syndrome (n=1; 2%) and post-partum haemorrhage (n=2; 5%). No maternal death was observed. There were 42 live births (98%) delivered at a median term of 38 27–42 WG with 9 (21%) before 37 WG and one medical termination of pregnancy for major IUGR at 21WG. IUGR was observed in 6 pregnancies (14%) associated with hypertension and pre-eclampsia or HELLP syndrome in 2 cases. The median birth weight was 2940 [610–4310] grams. Five children (12%) required intensive care units hospitalisation. One premature boy (27 WG) died after 2 days. Treatment during pregnancy included steroids (n=25/43, 58%), azathioprine (n=9/43; 21%) and infliximab (n=1/43; 2%). Pre-eclampsia were less frequent in patients treated with steroids during pregnancy (p=0.02). The risk of developing arterial hypertension was associated with previous chronic arterial hypertension, and an infra-diaphragmatic vasculitis injury (p=0.01 and p=0.04). Activity of TA was observed in the course of 12/43 pregnancies (28%). Conclusions: We observed both a high rate of obstetrical complications and of live birth. A preexisting chronic arterial hypertension, the infra-diaphragmatic location of vasculitis and/or an active disease in the 6 months preceding the pregnancy were associated with an impaired pregnancy outcome. TA disease activity did not seem to be influenced by pregnancy. Disclosure of Interest: None declared